Analyzing The Impact of Hope, Choice and Survey on The Level of Job Satisfaction of Employees at PT. Bank Indonesia Syariah (Persero) Banda Aceh Branch - Hajriyanti, Rahmi; Wani, Cut Eva (Indonesian Journal Economic Review (IJER), 2023)
This study aimed to determine the influence of hope, optimism, and resilience on the job satisfaction of employees at PT. Bank Indonesian Syariah (Persero). Banda Aceh Branch. This study was conducted in the city of Banda Aceh, with a sample of 106 respondents, where the sampling used as respondents was carried out in the form of a census, that is, taking the entire population. PT Bank Syariah Indonesia (Persero) Banda Aceh Branch is the defendant. The data analyzed in this study are primary data, specifically in the form of popular questionnaires. The data were then processed by multivariate linear regression analysis using SPSS. The subjects of this study are hope, optimism and resilience as independent variables. Meanwhile, the dependent variable of this study is job satisfaction. The results of this study show that simultaneously the variables hope, optimism and resilience have a significant impact on the job satisfaction variable. In part, only the hope and resilience variables have a significant impact on the job satisfaction variable.